PENGARUH PENGGUNAAN SERBUK ARANG TEMPURUNG KELAPA DAN VARIASI JUMLAH TUMBUKAN TERHADAP KARAKTERISTIK CAMPURAN BETON ASPAL - Mashuri, Mashuri (MEKTEK, 2008)
Using of charcoal dust of coconut shell in asphalt concrete mixture has been researched with some variations of number of blow to characteristic of asphalt concrete mixture type III.The aim of this research is to know characteristic of asphalt concrete mixture of type III which using charcoal dust of coconut shell with vary number of blow.Scenarios of variation of number of blow were twice of 75, twice of 100, twice of 200, and twice of 250 of blows. Scenarious of variation of charcoal dust of coconut shell content were 0%, 2%, 4%, 6% and 8%.Results of research showed that performance of stability, flow and durability of asphalt concrete mixture type III increase at using 2 % of charcoal dust of coconut shell with twice of 75 of blows. The more number of blows at asphalt concrete mixture of type III, tend to increase MQ value of asphalt concrete mixture for both with or without charcoal dust of coconut shell; which meant asphalt more stiff and tend to brittle, which it finally crash easily. The more number of blows and the higher percentage of charcoal dust of coconut shell in making specimen can decrease characteristic of durability of asphalt concrete.